RANCANGAN SETLING POND TERHADAP LAJU ENDAPAN SEDIMEN PADA AREA ARAFAH DAN WASTE DUMP PADA FRONT PENAMBANGAN PT. GAG NIKEL KAB. RAJA AMPAT PROVINSI PAPUA BARAT - Nofriyanto Towansiba; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
It is very important to know the design of the mine drainage system where to know the maximum rainfall each year, the extent of the catchment area, rainwater runoff discharge, sedimentation speed, open channel dimensions and sedimentation pond dimensions. The problem in this research is, how much is the catchment area, limited rainfall owned by the company, sedimentation speed, sedimentation pond dimensions and open channels. So that the results of the above problems are obtained, namely the extent of the arafah rain catchment area 103810,009 m2, waste dump I 256.901 m2, waste dump II 327172.506 m2. Runoff discharge at the area of 0.763 m3 / second, waste dump I 1,889 m3 / second, waste dump II 2,405 m3 / second. Sedimentation speed compressed 0,000365 m / s, open channel dimensions (neural area) I = 0.4 m, b = 0.45 m, t = 1.2 m, d = 0.7 m, h = 0.4 m. Waste dump area 1. I = 0.5 m, b = 0.63, t = 1.65 m, d = 1 m, h = 0.5 m. Waste dump area II. S = 600, I = 0.6 m, b = 0.7 m, t = 1.8 m, d = 1.1 m, h = 0.6 m. Dimension of arafah settling ponds, 2091.063974 m2, waste dump I, 5174, 822463 m2, waste dump II, 6590, 295552 m2. For sump dimensions with a depth of 2 meters, a leght of 56,42 meters and a width of 26,40 meters with a volume of 2450,444 m